2011
DOI: 10.1016/j.aip.2010.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Dancing, moving and writing in clinical supervision? Employing embodied practices in psychotherapy supervision

Abstract: This paper takes a new look at the methods of embodiment for psychotherapy supervision. It makes a rigorous distinction between knowledge derived via language and knowledge derived via the body without the intervention of conscious thought and above all language.In an account of a study whereby the principal researcher and her co researchers, all professional practitioners of dance movement psychotherapy, the genesis and development of new tools designed to capture the connection between movement and the possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…Using art in the supervision space even reduces tension (Deaver & Shiflett, 2011); improves the relationship between supervisor and supervisee (Scheiby, 2001); increases self-awareness in the supervisee (Austin & Dvorkin, 2001); and increases empathic attunement (Cooper, 2001). The importance of using the body and its movement in therapy and supervision, as a way of understanding and knowing, has been mentioned by a number of dance movement therapists (Federman, 2011;Meekums, 2007;Panhofer et al, 2011;Payne, 2008). Payne (2008) emphasized the contribution of using writing, moving, or visual art to gain new perspectives on the supervision material.…”
Section: Authentic Movementmentioning
confidence: 99%
See 4 more Smart Citations
“…Using art in the supervision space even reduces tension (Deaver & Shiflett, 2011); improves the relationship between supervisor and supervisee (Scheiby, 2001); increases self-awareness in the supervisee (Austin & Dvorkin, 2001); and increases empathic attunement (Cooper, 2001). The importance of using the body and its movement in therapy and supervision, as a way of understanding and knowing, has been mentioned by a number of dance movement therapists (Federman, 2011;Meekums, 2007;Panhofer et al, 2011;Payne, 2008). Payne (2008) emphasized the contribution of using writing, moving, or visual art to gain new perspectives on the supervision material.…”
Section: Authentic Movementmentioning
confidence: 99%
“…Payne (2008) emphasized the contribution of using writing, moving, or visual art to gain new perspectives on the supervision material. Panhofer et al (2011) even suggested a new method of selfsupervision involving movement. Meekums (2007) uses the body as a central listener in DMT supervision, who is waiting to absorb information, bypassing the logical area of the brain and activating the body's wisdom.…”
Section: Authentic Movementmentioning
confidence: 99%
See 3 more Smart Citations